Low Ki-67 gene expression in non-neoplastic proliferation of oral mucosal epithelium - Janti Sudiono; Irmawati Hassan (Universa Medicina, 2012)
BACKGROUNDNeoplastic and non-neoplastic oral mucosal growths often have a variety of clinical manifestations according to their biological nature. Immunohistochemical diagnostic markers, such as Ki-67, are used to detect their proliferation and differentiation. Ki-67 is expressed in all phases of the cell cycle, except G0. The objective of this study was to determine Ki-67 expression in benign, malignant and non-neoplastic proliferation of oral mucosal epithelium.METHODSA laboratory study of cross sectional design was conducted using samples from excised oral mucosa diagnosed as inflammatory gingival hypertrophy (n=5); epulis (n=6); gingival polyps (n=5); pulpal polyps (n=5); papilloma (n=3) and squamous cell carcinoma (n=2). The antigen retrieval endogenous peroxidaseblock method was used in the application of Ki-67 primary  antibody and chromogen to display the antigen antibody reaction, with positive  cells showing brown nucleoplasm staining. The Ki-67 positive index was calculated by dividing the number of positive epithelial cells with the total number of epithelialcells in the areas observed at 400x magnification. One-way ANOVA was used to compare the Ki-67 indexes of neoplastic and non-neoplastic lesions.RESULTSThe highest Ki-67 positive index was for squamous cell carcinoma (64.55 ± 23.55%) followed by papilloma (23.33 ± 6.94%), gingival polyps (7.06 ± 7.43%) and gingival hypertrophy (1.40 ± 2.80%). One-way ANOVA showed significant differences in Ki-67 expression between neoplastic and non-neoplastic  samples (p<0.05).CONCLUSIONSThe high Ki-67 expression in neoplasms is proportional to the  grade of malignancy. In non-neoplastic processes Ki-67 expression is merely an adaptive response and does not indicate increased Ki-67 proliferative gene expression.